The impact of structural context on local crime control strategies and media attentiveness to crime - Smith, Dani Allred (2001)
A neo-Marxist approach has been utilized to explain variation in local crime control strategies and media attentiveness to crime. The present study has argued that increased crime control and media attentiveness to crime result from perceived threats to the economic and social order by subordinate classes rather than from increases in the crime rate. The entire analysis has required two seperate methodologies. First, a panel design and residual change regression analysis were used to examine 396 cities from 1950 to 1970. This analysis was used to determine the effect of changes in social and economic variables on changes in police size and police expenditures